(untitled) (Zaporizhzhia Historical Review, 2021)
In this article the author analysed the contribution of statisticians Kherson’s zemstvo 1880-s years into development of theory and practice historical regionalistic in Ukraine. The author discover ways to realization of conception «oblasnytstvo» in creative heritage kherson’s statisticians.